PANDALUNGAN SEBAGAI TITIK TEMU: INTERAKSI EKONOMI DAN DAKWAH ISLAM DALAM SEJARAH LOKAL - rosidah, 21_mahfufatur; Halid, Ahmad (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2025)
Abstract: This study aims to examine the role of the Pandalungan region as a center of interaction between economic activities and the spread of Islamic da’wah from a local historical perspective. Using a qualitative approach through historical study, the research draws on sources from literature, interviews with community leaders, and observations of historical sites. The findings reveal that trade routes served as effective channels in the process of Islamization, where Muslim traders acted as da’wah agents through ethical business practices and social interactions. Da’wah within this community occurred in a cultural, adaptive, and non-confrontational manner. The Pandalungan people integrated Islam into their local traditions, resulting in a distinctive and contextual expression of Islam. This study highlights the importance of culturally and economically based da’wah strategies in the success of past Islamization efforts, which remain relevant in the present context. Keywords: Pandalungan, Islamic Da’wah, Trade Routes Abstrak: Penelitian ini bertujuan untuk mengkaji peran wilayah Pandalungan sebagai pusat interaksi antara kegiatan ekonomi dan penyebaran dakwah Islam dalam perspektif sejarah lokal. Dengan pendekatan kualitatif melalui studi historis, penelitian ini memanfaatkan sumber dari literatur, wawancara dengan tokoh masyarakat, serta observasi terhadap situs bersejarah. Temuan penelitian mengungkap bahwa jalur perdagangan berfungsi sebagai sarana efektif dalam proses Islamisasi, di mana para pedagang Muslim berperan sebagai penyebar dakwah melalui prinsip bisnis yang etis serta interaksi sosial. Dakwah dalam komunitas ini berlangsung secara budaya, adaptif, dan tanpa konfrontasi. Masyarakat Pandalungan mengintegrasikan Islam ke dalam tradisi lokal mereka, menghasilkan bentuk keislaman yang khas dan kontekstual. Studi ini menekankan pentingnya strategi dakwah berbasis budaya dan ekonomi dalam keberhasilan Islamisasi masa lampau, yang tetap relevan dalam situasi saat ini. Kata Kunci: : Pandalungan, Dakwah Islam, Jalur Perdagangan